IDEALISTIC AND IDEOLOGY ISLAMIC CONCEPTS IN WAHHABI SAUDI ARABIA - Sa’bana, Sofia Mubarokah; Navlia, Rusdiana; Rahmawati, Siti (INTIHA: Islamic Education Journal, 2025)
This research focused on religious purification, an understanding rejecting the taqlid offered by fiqh and theology in traditional Islamic knowledge, and aims to restore all existing problems to the true sources of Islam, Al-Qur'an, and Sunnah. This is one reason that triggered the birth of the Wahhabi movement, which is still developing in Saudi Arabia, where the Wahhabi movement has the largest ideology. This research used qualitative descriptive research with the literature review method. The researcher described Islamic idealism and ideology in the Wahhabi concept, especially as it developed in Saudi Arabia. The data source was books or journals related to Wahhabi ideology in Saudi Arabia. The results of data searches using this method show that researchers collected data that will be used in reviewing and completing every part of the data in the study that is analyzed. Then, I marked important data, noted them down, and selected them according to needs and those related to this research. After data is collected, the approach used in analyzing various problems is historical, namely by classifying and studying data in Wahhabi ideology.